Impacts of Global Change on Ocean Dissolved Organic Carbon (DOC) Cycling - Lønborg, Christian; Carreira, Cátia; Jickells, Tim; Álvarez-Salgado, Xosé Antón (Frontiers in Marine Science, 2020)
The marine dissolved organic carbon (DOC) pool is an important player in the functioning of marine ecosystems. DOC is at the interface between the chemical and the biological worlds, it fuels marine food webs, and is a major component of the Earth’s carbon system. Here, we review the research showing impacts of global change stressors on the DOC cycling, specifically: ocean warming and stratification, acidification, deoxygenation, glacial and sea ice melting, changed inflow from rivers, changing ocean circulation and upwelling, and wet/dry deposition. A unified outcome of the future impacts of these stressors on the global ocean DOC production and degradation is not possible, due to regional differences and differences in stressors impacts, but general patterns for each stressor are presented.